Kualitas Produk dan Citra Merek: Keputusan Pembelian Konsumen Susu Dancow di Kota Medan - Rahmad Efendy; Infensius Gea; Anggi Dian Safitri; Bayu Teta (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This study aims to examine the influence of product quality and brand image on consumer purchasing decisions of Dancow milk in Medan City. The research employs a quantitative approach using multiple linear regression analysis with SPSS version 26. The sample consists of 65 respondents determined using the Hair , method, and data were collected through questionnaires. The t-test results indicate that product quality does not have a significant effect on purchasing decisions Sig. 0.093, while brand image has a significant influence Sig. 0.000. The F-test shows that product quality and brand image simultaneously have a significant effect on purchasing decisions Sig. 0.000. The Adjusted R Square value of 0.218 indicates that 21.8% of the purchasing decision variable is explained by the two independent variables. Therefore, brand image is the dominant factor influencing consumer purchasing decisions for Dancow milk in Medan City.